Irrigation, risk aversion, and water right priority under water supply uncertainty - Li, Man; Xu, Wenchao; Rosegrant, Mark W. (American Geophysical Union, 2017)
This paper explores the impacts of a water right's allocative priority—as an indicator of farmers' risk-bearing ability—on land irrigation under water supply uncertainty. We develop and use an economic model to simulate farmers' land irrigation decision and associated economic returns in eastern Idaho. Results indicate that the optimal acreage of land irrigated increases with water right priority when hydroclimate risk exhibits a negatively skewed or right-truncated distribution. Simulation results suggest that prior appropriation enables senior water rights holders to allocate a higher proportion of their land to irrigation, 6 times as much as junior rights holders do, creating a gap in the annual expected net revenue reaching up to $141.4 acre−1 or $55,800 per farm between the two groups.